ANALISIS LITERATUR : PENGARUH MULTIMEDIA INTERAKTIF TERHADAP BEBAN KOGNITIF DALAM PEMBELAJARAN - Melati, Melati Puspa Kencana; Fadilah, Muhyiatul (Jurnal Biogenerasi, 2025)
This study aims to analyze the effect of interactive multimedia on cognitive load in learning, especially in the context of biology education. The study was conducted through a literature review method by examining seven scientific articles consisting of four international publications and three national publications. Data were collected through the Google Scholar platform using the keywords “the effect of interactive multimedia on cognitive load” and “interactive multimedia learning.” The results of the analysis show that interactive multimedia designed based on cognitive load theory and multimedia learning theory can reduce students' cognitive load, improve concept understanding, and make the learning process more efficient. Thus, the application of interactive multimedia is an effective strategy in supporting meaningful learning in the digital age.